Transformasi Pembelajaran Biologi melalui Artificial Intelligence (AI) untuk Penguatan Keterampilan Abad 21 - Remindima, Ferdinand Ndawa Lu; Marleni Rosalia Ndapa Huda (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the transformation of Biology learning through the integration of Artificial Intelligence (AI) to strengthen 21st-century skills at a State Senior High School in Waingapu, East Sumba. Amidst the limitations of physical laboratory facilities, AI emerges as an innovative solution to visualize abstract biological concepts. This research employs a qualitative approach, with data collection techniques involving observation, interviews with teachers and students, and documentation studies. The results indicate that the utilization of AI platforms, such as Generative AI and virtual simulations, significantly shifts the student learning paradigm from rote memorization to active inquiry. The integration of AI has proven effective in reinforcing the 4C skills (Critical Thinking, Creativity, Collaboration, and Communication). Students have become more critical in validating information, creative in designing science projects, and more collaborative in classroom discussions. Furthermore, AI assists teachers in streamlining instructional time, allowing for deeper conceptual exploration. Despite challenges regarding local internet stability, this transformation represents a strategic step in narrowing the educational quality gap between peripheral and urban areas. In conclusion, the implementation of AI, coupled with adaptive teacher guidance, is highly effective in developing competitive students in the digital era.